Exchange rate effects of a potential Brexit on German-UK bilateral trade - Stella Capuano; Ignat Stepanok (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2016)
In this report we look at German-UK bilateral trade in goods and estimate the short-run sensitivity of imports and exports of Germany and the UK to exchange rate movements.
Keywords: 330